(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2017)
Researches were made for the purpose of increase of labor productivity and replace of non ferrous metals and ferrous metals by plastics. Details for this purpose are selected with a certain characteristic that further the developed technological process could be applied in the oil and gas industry.Plastic materials have the difficult intense nature and differ from metals markedly the expressed deviations from property of ideally elastic solid bodies.